Socio-Economic Status of Kingariya : (A Case Study of Nepalgunj Sub-Metropolitan - 22, Puraini, Banke) - D C, Daman Dhoj (Academia Research Journal, 2023)
Analyzing the socioeconomic situation and current circumstances of the Kingariya community of Dalit Muslims in Puraini, Nepalgunj, was the goal of this study. They are a group of traditional dancers and cultural performers from the upper caste of Muslims. Muslims from the Dalit community work as wage laborers in agriculture and construction. Despite spending a lot of time in the Terai region of Nepal, they are poor and landless. The primary goal of this study is to examine the socioeconomic situation of the Kingariya community in Kingariyanpurwa, Puraini, in the Banke district. In this study, a descriptive and exploratory research design was used. The socioeconomic situation of the Kingariya people is generally described in chronological sequence in this study design. Both primary and secondary data are used in this investigation. Interviews were used to gather primary data from the field survey, while secondary data came from the Nepalgunj Sub-Metropolitan Office, private agencies, government offices, numerous research publications, and other pertinent literature and websites on the internet. The 26 Dalit Muslim households in this study area make up the study’s target population. To determine the socioeconomic status of the dalit Muslim community, a purposeful sample technique was chosen. The small population of Dalit Muslims lives in Puraini, Nepalgunj. In the 56 total households for the household survey, there were 26 Kingariya households, or 50% of all households. The study’s conclusion is that Muslims live in a socioeconomically deplorable situation. They are hardworking, straightforward, and illiterate, yet they are also poor. High cast has complete control over them in all aspect of life. The socioeconomic status of the Muslim population has had both positive and negative effects over time.